Sin licenses revisited - Markus Haavio; Kaisa Kotakorpi (Center for Economic Studies and ifo Institute (CESifo), 2012)
We analyse attempts to implement personalised regulation in the form of sin licenses (O'Donoghue and Rabin 2003, 2005, 2007) to correct the distortion in the consumption of a harmful good when consumers suffer from varying degrees of self-control problems. We take into account the possibility that consumers may trade the sin good in a secondary market, and show that sin licenses induce only sophisticated individuals with low levels of self-control problems to consume optimally. The consumption of naive individuals as well as sophisticated individuals with severe self-control problems remains too high, and welfare in equilibrium is decreasing in the level of self-control problems and non-increasing in the level of naivete. Further, we show that introducing a uniform tax on top of a system of sin licenses may improve welfare, whereas a uniform maximum quota would reduce welfare for sophisticates but may increase welfare for naives. Finally, we show that naives would benefit from a scheme where sin licenses are sold for a positive price in the primary market.
Keywords: H21; H30; I18; 330; self-control problems; sin licenses; secondary markets